T. Veblen's Theory of Conspicuous Consumption and Problems of Modern Culture and Consumption Analysis - Čemevičiūtė, Jūratė (Problemos, 2003)
The article analyses the classical theory of conspicuous consumption developed by American economist Thorstein Veblen. For better understanding of this theory, the social reality of the Gilded Age in U. S. (1860-1914) is discussed as Veblen's source of inspiration and direct object of his theory. The article includes historically comparative survey of different forms of conspicuous consumption in traditional and modern societies. The patterns of conspicuous consumption are compared with other forms of exceptional behaviour. The concluding part of the article discusses the reception of Veblen?s ideas in the economic and sociological theories of consumer behaviour and highlights their shortcomings and blind spots which can be explained mainly by the limits of the social experience which served as Veblen's source of inspiration.
Keywords: conspicuous consumptions; the models of consumption in traditional and modern society; "Veblen"; "bandwagon"; "snob" effects in the contemporary theories of consumer behaviour